VISUAL ANALISIS PADA SAMPUL MAJALAH TEMPO EDISI 14 SEPTEMBER 2019 (SEMIOTIKA ROLAND BARTHES) - PInontoan, Nexen Alexandre (Universitas Budi Luhur, 2023)
This study aims to explain how the cover of Tempo magazine depicts Jokowi in visual reality and explains how the cover of the September 14 2019 edition of Tempo magazine is analyzed through Roland Barthes' semiotics. The research question posed is How is the semiotic analysis on the cover of the September 14 2019 issue of Tempo magazine analyzed using Roland Barthes' semiotics. This research method is qualitative with Roland Barthes semiotic analysis. The subject of the research is the cover of Tempo magazine. Data collection was obtained through observation, using primary and secondary data collection techniques. The data obtained directly from the research object, namely the cover of Tempo magazine. The results of the study show that the representation of capitalism from the cover of Tempo magazine uses signs, through text, pictures and scenes. Tempo must compete in the digital era as it is today in order to maintain its position at the level of other media capitalists. Dissecting the ideological elements on the cover of this magazine uses Roland Barthes' semiotic analysis. At the stages of denotation, connotation and myth, one can see the content of the ideology of capitalism on the cover of the magazine. The ideology embedded in this cover is illustrated through the character of Jokowi, businessmen and parties, namely the owners of power and the economy. the lighting, scene, setting and props in this cover also identify the capitalist system. The capitalist system that already exists within the government, forces the public to submit to the rules given by the capitalists. The rise of new media also creates competition without regard to the legitimacy of news value. The cover of this magazine provides a representation of the condition of Indonesia, that the ideology of capitalism dominates the industry, for owners of capital and those in power can easily determine market prices and dominate the people. Roland Barthes' semiotic theory is precise in discovering the ideological elements embedded in the Cover of Tempo Magazine.